2019
DOI: 10.1109/tcbb.2018.2822675
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Prostate Cancer from Benign Prostatic Hyperplasia Using PSAD Based on Machine Learning: Single-Center Retrospective Study in China

Abstract: The incidence of prostate cancer increases annually. Prostate cancer is an underreported and emerging problem in China. We conducted a cross-sectional study of 392 eligible patients from 710 men with prostate cancer or benign prostatic hyperplasia between 2000 and 2003. For total prostate-specific antigen, age, three diameters of prostate, prostate volume and prostate-specific antigen density seven indices, analysis of variance and t test were used to analyze the difference between the groups. A decision tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Yi-Yan Zhang et al. ( 21 ) reported a PSA density (PSAD)-related ML method that enhanced the detection rate of PCa (sensitivity: 0.866; specificity: 0.781), while our P504s/P63-related ML technique further improved upon this diagnostic performance. However, we found that the models showed good specificity and accuracy (0.980, 0.831) but poor sensitivity (0.333) for label 0.…”
Section: Discussionmentioning
confidence: 99%
“…Yi-Yan Zhang et al. ( 21 ) reported a PSA density (PSAD)-related ML method that enhanced the detection rate of PCa (sensitivity: 0.866; specificity: 0.781), while our P504s/P63-related ML technique further improved upon this diagnostic performance. However, we found that the models showed good specificity and accuracy (0.980, 0.831) but poor sensitivity (0.333) for label 0.…”
Section: Discussionmentioning
confidence: 99%
“…Authors in [ 31 ] exploit supervised machine learning to detect patients afflicted with prostate cancer. By exploiting features related to volume, age and prostate-specific indicators they obtain a prostate cancer detection rate equal to 86.6%.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Compensating for the limitations of PSA tests is achieved by adjusting PSA levels according to prostate volume (PV), known as PSA density (PSAD). [7, 8]…”
Section: Introductionmentioning
confidence: 99%